How to improve an Open Access Books collection’s considering user’s demands - Meletiou, Aristeidis; Katsirikou, Anthi (Qualitative and Quantitative Methods in Libraries; Vol 6 No 1 (2017): March 2017 Issue, 2019)
In modern Libraries one of the most important offered services is the ability for users to use open access books’ collection to satisfy their needs and expectations. The improvement procedure of an open access books collection needs specific attention as it is fact that is a vital issue of a modern Library. This particular work tries to show how Librarians can consider user’s demands to improve efficiently an open access books collection. It describes the way of collecting data about user’s demands, how can be analyzed properly and how can be considered by Librarians when they try to improve an existed open access books collection or to build a new one.  User demands can be applied from respective surveys that can be applied in many ways. This paper shows the proper ways of conducting surveys for estimation of user’s demands. Furthermore it describes a way of collecting users’ requests about Open Access Books and finally the methodology combines above information for helping Librarians to build a final priority list of Open Access Books that can be acquired. The goal of presented study is to help Library decision makers to take right decisions about what actions can do to improve efficiently “open access books collection” in their Library Organization